2020
DOI: 10.3389/fpls.2020.01142
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the 1-Deoxy-D-Xylulose 5-Phosphate Synthase Genes in Morus notabilis

Abstract: Terpenoids are considered to be the largest group of secondary metabolites and natural products. Studies have revealed 1-deoxy-D-xylulose 5-phosphate synthase (DXS) is the first and rate-limiting enzyme in the plastidial methylerythritol phosphate pathway, which produces isopentenyl diphosphate and its isoform dimethylallyl diphosphate as terpenoid biosynthesis precursors. Mulberry ( Morus L.) is an economically and ecologically important perennial tree with diverse secondary metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…An analysis of the subcellular localization of the proteins showed that SlDXS proteins are all predicted to be localized in the chloroplasts. This is consistent with the fact that the three DXS genes of Morus notabilis are located in chloroplasts [36]. The MEP pathway occurs in plastids, so it is reasonable that the SlDXS genes are located in chloroplasts [36].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…An analysis of the subcellular localization of the proteins showed that SlDXS proteins are all predicted to be localized in the chloroplasts. This is consistent with the fact that the three DXS genes of Morus notabilis are located in chloroplasts [36]. The MEP pathway occurs in plastids, so it is reasonable that the SlDXS genes are located in chloroplasts [36].…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with the fact that the three DXS genes of Morus notabilis are located in chloroplasts [36]. The MEP pathway occurs in plastids, so it is reasonable that the SlDXS genes are located in chloroplasts [36]. It was found that the DXS gene family contains three subfamilies, namely DXS I, DXS II, and DXS III, each with different functions [33].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several genes identified within the validated hotspot regions encode enzymes involved in various metabolic processes, such as terpenoid biosynthesis (1-deoxy-D-xylulose-5-phosphate reductoisomerase) ( Zhang et al, 2020 ), auxin dependent endomembrane homeostasis (1-phosphatidylinositol-3-phosphate 5-kinase ( Lo et al, 2022 ), oil biosynthesis (acyltransferase) ( Yan et al, 2018 ), photorespiration (alanine--glyoxylate transaminase which is known to facilitate the transamination between L-alanine and glyoxylate to produce pyruvate and glycine) ( Liepman et al, 2019 ), lipid metabolism (aspartic proteinase oryzasin-1) ( Alexandrov et al, 2009 ), carbohydrate metabolism (endoglucanase) ( Jiao et al, 2017 ), sugar isomerization (epimerase domain-containing protein), phosphorus remobilization (glycerophosphodiester phosphodiesterase) ( Wang J. et al, 2021 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was reported by Cordoba et al (2011) who demonstrated plastid localization in Z. mays leaves. DXS catalyzes the first reaction that converts pyruvate and glyceraldehyde-3-phosphate to 1-deoxy-D-xylulose 5-phosphate in the methylerythritol phosphate pathway (Tambasco-Studart et al, 2005;Zhang et al, 2020). The remaining cluster 5 and nodes, namely, 7, 10, 11, and12 (Table 2), do not cover up the pathways under the high scoring method within the top 100 (Supplementary Table S15).…”
Section: Protein-protein Interaction Network Establishment In the Inf...mentioning
confidence: 99%